Synthesis, characterization, and biological activity of novel azole piperazine congeners - Priyanka R. Sadalge, Vrushabh Karnawadi, Lairikyengbam Deepti Roy, Manikanda Prabu, Geeta Krishnamurthy, Pooja Gour, Shivanjali Esther Arland, Jyotsna Kumar (Journal of Applied Pharmaceutical Science, 2023)
A novel series of piperazine analogs were synthesized comprising azole moieties with good yield. Structures of all four synthesized azole analogs were established by spectral characterization viz 1H-nuclear magnetic resonance, liquid chromatography-mass spectrometry, and FT-IR. Synthesized derivatives were further assessed for their antimicrobial and antioxidant studies. Antimicrobial activity was conducted against Pseudomonas aeruginosa, Staphylococcus aureus, and Candida albicans by well diffusion method. The antimicrobial activity reflects that synthesized piperazine derivatives containing imidazole moiety possess better antibacterial and antifungal activity than piperazine analogs comprising triazole moiety. Staphylococcus aureus exhibited strong resistance over all synthesized piperazine derivatives. Antioxidant activity of synthesized molecules was carried out by using 1, 1-diphenyl-2-picrylhydrazyl. In vitro, antioxidant activity results revealed that IC50 values of synthesized piperazine analogs are comparative with control—gallic acid whereas piperazine derivatives with triazole unit ITZ-1 and ITZ-2 are exhibiting better antioxidant activities. Hence, synthesized novel molecules with better antimicrobial and antioxidant activities may be further used in the formulation of new antimicrobial and antioxidant drugs. Observed IC50, zone of inhibition values, and drug resistance of S. aureus strain against all synthesized novel piperazine derivatives in the present investigation will be helpful to be used as a reference for auxiliary studies and further evaluation is worth developing a new generation drug.